Related Pathological and Social Factors that Delay Early Detection of Breast Cancer among Females - Al-Hakak, Asmaa; Mohammed, Halah (Journal of Biomedicine and Biochemistry, 2022)
The current study aimed at assessing the factors that hinder early detection of breast cancer among women, and to identify the association between socio-demographic characteristics and women's knowledge about ways of early detection and causes for delay in seeking medical help.Methodology: A descriptive design/correlation study is used throughout the present study. A Non-Probability (Purposive Sample) of (150) women with third and more stages of breast cancer (advanced breast cancer) was selected. The data are collected through the utilization of the developed questionnaire by using an interview technique after the estimation of the validity and reliability of the study instrument.Results: the correlation between overall women's knowledge about ways of early detection and their demographic data, shows that overall women's knowledge has a significant positive correlation with each of age, family history of breast cancer, and level of education. The result also indicates that the correlation between causes for delay in seeking medical intervention and women demographic data. It shows that there is a significant positive correlation with each of residence and family history of breast cancer and most patients are delayed in seeking medicine because of lack of awareness and financial problems.Conclusion: The study concluded that the general assessment is moderate knowledge about early detection of breast cancer among women, and found a significant relationship between family history and residence with knowledge of patient while there is no correlation with other demographic data.